Asymptotic versus bootstrap inference for inequality indices of the cumulative distribution function - Ramses H. Abul Naga; Christopher Stapenhurst; Gastón Yalonetzky (Econometrics, 2020)
We examine the performance of asymptotic inference as well as bootstrap tests for the Alphabeta and Kobus-Mi±os family of inequality indices for ordered response data. We use Monte Carlo experiments to compare the empirical size and statistical power of asymptotic inference and the Studentized bootstrap test. In a broad variety of settings, both tests are found to have similar rejection probabilities of true null hypotheses, and similar power. Nonetheless, the asymptotic test remains correctly sized in the presence of certain types of severe class imbalances exhibiting very low or very high levels of inequality, whereas the bootstrap test becomes somewhat oversized in these extreme settings.
Keywords: 330; large sample distributions; measurement of inequality; monte carlo experiments; multinomial sampling; ordered response data; Studentized bootstrap tests